Development And Implementation of Infiltration Wells in 9 Districts of Sidoarjo Regency, Indonesia - Akhmad Yusuf ZUHDY (Smart Cities and Regional Development Journal, 2023)
The area of ??Sidoarjo Regency consists of 18 districts with a land area of ??around 714,245 km2 and a coastal area of ??around 201,687 km2. The topographical conditions in the Sidoarjo Regency are lowlands with altitudes ranging from 0 to +25 m above sea level, so that certain areas in Sidoarjo Regency show a condition that has the potential to experience flooding problems. Making infiltration wells is one of the most efficient solutions. Infiltration wells are wells or holes on the ground surface that are made to collect rainwater so that it can seep into the ground either through the roofs of buildings, roads and yards. There are 20 points spread across 9 sub-districts in Sidoarjo Regency which, based on field survey reviews, have the potential to experience flooding problems. In this area, infiltration wells will be built. Direct observation in the field is carried out to determine the condition of the area under review and to plan the design and recommendation points to be carried out. In addition to this, soil permeability conditions also need to be analyzed so that the coefficient is known. Primary data collection related to soil type classification was obtained from literacy data and soil type maps in Sidoarjo Regency. Based on direct observation and soil type literacy data, it is recommended that infiltration wells with a depth of 2 meter and a diameter of 1.1 meter be used are buis concrete and a filter system using palm fiber as a filter for sediment and waste so as not to interfere with the infiltration process in the infiltration well. 1 infiltration well can accommodate and absorb ± 1900 liters of water which can reduce flood discharge within 46 to 61 hours depending on the type of soil under review.